2013
DOI: 10.3109/10837450.2013.784336
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the effect of sonication parameters on size and dispersion temperature of solid lipid nanoparticles (SLNs) by response surface methodology (RSM)

Abstract: The objective of this study was to evaluate the effect of sonication time and pulse frequency on average dispersion temperature (ART), particle size and zeta potential of solid lipid nanoparticles (SLNs). A two-factor, three-level response surface methodology (RSM) was used to optimize sonication time between 5 and 15 min and pulse frequency from 30 to 90%. SLNs made from stearyl alcohol (SA) and cetyl trimethylammonium bromide (CTAB) blend at 1:3 ratio were prepared by applying high-shear homogenization and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 19 publications
1
26
0
1
Order By: Relevance
“…It was observed that as sonication time was increased from 1 min to 12.5 min, the particle size was gradually decreased which might be attributed to energy provided by sonication which reduced the size of coarse dispersion into nano-droplets [18]. Entrapment efficiency was not significantly affected by sonication time upto 10 min.…”
Section: Influence Of Homogenization Timementioning
confidence: 74%
See 2 more Smart Citations
“…It was observed that as sonication time was increased from 1 min to 12.5 min, the particle size was gradually decreased which might be attributed to energy provided by sonication which reduced the size of coarse dispersion into nano-droplets [18]. Entrapment efficiency was not significantly affected by sonication time upto 10 min.…”
Section: Influence Of Homogenization Timementioning
confidence: 74%
“…Sonication works by producing cavitation transit in the dispersion and its effectiveness depends on viscosity and density of dispersion which in turn is affected by formulation temperature. It is essential to maintain temperature above melting point of lipid to facilitate breakdown of dispersion [18]. The results showed that at 20 to 40% sonication amplitude, particle size was more than 200 nm indicating that low intensity of sonication was unable to reduce particle size efficiently.…”
Section: Influence Of Homogenization Timementioning
confidence: 91%
See 1 more Smart Citation
“…It is known that a zeta potential of ±30 mV is able to stabilize nanoparticle formulations. 37,38 In this test, the zeta potential of the nanoparticles emulsion was -28.7±1.94 mV, which was efficient in stabilizing the system.…”
Section: Particle Size and Zeta Potential Analysesmentioning
confidence: 99%
“…Moreover, the shockwaves can create high velocity inter-particle collisions. 21 In this way, when the surfactant content is increased, the low level of power input is enough for inhibition of the particles size growth, but the continuous increase in the power input and cycles would probably cause damages to the stabilizer layer and might induce agglomeration and particles size increase. 20 The particle size of nanosuspensions was also affected by the interaction of solid content and the time interval of acid addition.…”
Section: Discussionmentioning
confidence: 99%